Assessment of heavy metals pollution in sediment of Citarum River, Indonesia - Yenny, Mutia Oktarina Permai; Arief Hartono; Syaiful Anwar; Yumei Kang (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
Heavy metals have been reported to accumulate in sediment of Citarum River. The measurement of total heavy metals may not be able to provide information about the exact dimension of pollution, thus the determination of different fractions assumed great importance. This study was performed to determine chemical fractions of heavy metals (Cu, Ni, Cr, Pb and Cd) in sediment collected at 8 locations from Citarum River. The sequential extraction procedure was used to extract heavy metals in water-soluble, acid-soluble, MnO occluded, organically bound, FeO occluded and residual fraction in sediment. Bioavailability and potential ecological risk level of heavy metals were evaluated based on bioavailability factor (BF) and risk assessment code (RAC) method. The results showed that Cu, Ni, Cr were mostly in residual form, indicate those from geological sources. Cu had low bioavailability and no risk in all sediment samples of Citarum River. Ni and Cr each was found to have risk at 2 locations. Pb and Cd were found dominantly in non-residual fraction, suggest those from anthropogenic sources. BF and RAC analysis of Pb and Cd suggest that there is a potential risk to the aquatic environment.